Evaluación formativa y habilidades matemáticas en los estudiantes de la Institución Educativa Ceba Miguel Acosta Oyarce, Caballococha Provincia Mariscal Ramón Castilla 2023 - Rojas Tovar, Nancy María (2024)
The main objective of this research was to determine the relationship between formative evaluation and the mathematical skills developed in the students of the CEBA educational institution, Miguel Acosta Oyarce, located in Caballo Cocha, Province of Ramón Castilla. The study sample consisted of 227 students and a quantitative approach guided by a basic research of non-experimental design was used to evaluate this relationship. The data were analyzed statistically, showing a Kendall's Tau-c coefficient of 0.618 and a p-value of 0.000, which indicates a significant relationship (p<0.05) between the formative evaluation and the mathematical skills developed by the students. students. This suggests that when teachers integrate formative assessment factors into their teaching, students tend to better develop their mathematical skills. In conclusion, the research establishes that there is a positive and significant relationship between formative assessment factors and the development of mathematical skills in students.